PEMANFAATAN MEDIA PEMBELAJARAN ASSEMBLR EDU DALAM MENGEMBANGKAN SIKAP KEBERSAMAAN SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Aprida Nisa Ainisyifa; Dede Iswandi; Intan Indah Megasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the use of Augmented Reality-based Assemblr Edu learning media in developing students' sense of togetherness in Pancasila Education. This study used a literature review method by reviewing various journals, books, and relevant previous research results. The results of the study indicate that the use of Assemblr Edu can create more interactive, engaging, and contextual learning through Augmented Reality features and three-dimensional visual displays.